A Model for Negotiations about Exchanges Values in Multiagents Systems - Franco, Márcia Häfele Islabão; Costa, Antônio Carlos da Rocha (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2007)
This paper presents dialogue protocols based on argumentation and focused to on the establishment of social exchanges values. In the definition of the protocols’ model, we adopt the Piaget’s theory of social exchanges, where an interaction is an exchange of services between agents. The model enables the agents, involved in interactions, to negotiate with each other about the exchange values. In consequence, the agents become able to choose in a sounder way whether they will continue to make part of the particular social group with which they interact, and also who will be their future partners in such group. Such exchange values constitute, thus, a social regulation tool which the set of agents can use in an effort to guarantee the stability of their social interactions.